Binding of aldehyde flavour compounds to beef myofibrillar proteins and the effect of nonenzymatic glycation with glucose and glucosamine. (June 2021) - Dou, Peipei; Feng, Xianchao; Cheng, Xingguang; Guan, Qinhao; Wang, Junlan; Qian, Shan; Xu, Xinglian; Zhou, Guanghong; Ullah, Niamat; Zhu, Beiwei; Chen, Lin
Abstract: The effects of nonenzymatic glycation on the binding capacity of beef myofibrillar proteins (MP) to aldehyde flavour compounds were investigated. The binding capacity was significantly increased due to the partial unfolding and flexible secondary structure of the glycated MP. Unfolding played a dominant role in binding due to the prevention of protein aggregation by steric hindrance originating from glycation with glucose (Glu), while glycation with glucosamine (GluA) induced substantial aggregation due to cross-linking. Therefore, the MP glycated with Glu had a higher binding capacity for aldehyde flavour compounds compared to MP glycated with GluA. In a competitive binding system, the MP glycated with Glu had a higher binding capacity for long-chain aldehyde flavour compounds. However, the MP glycated with GluA had a higher binding capacity for short-chain aldehyde flavour compounds, which were more likely to interact with the binding sites shielded in the protein aggregate. Nonenzymatic glycation represents a potential method to enhance the flavour intensity of meat products with high-protein levels. Graphical abstract: Image 1 Highlights: Nonenzymatic glycation led to more flexible structure of myofibrillar proteins. Glycation with glucosamine induced the dramatic cross-linking of proteins. Glucose-glycated proteins had a higher binding capacity for nonanal. Glucosamine-glycated proteins had a higher binding capacity for heptanal.